The Principal's Commitment to Achieving Management Success at Integrated Islamic Junior High Schools in the Riau Islands Province - M. Tholibin Azhari; Mukhtar Latif; M.Syahran Jailani (PT. Anagata Sembagi Education, 2026)
This study examines the principal's commitment to achieving successful management at SMPIT AI-Madinah, Tanjung Pinang City, SMPIT Cendekia, Karimun Regency, and SMPIT BP Tahfidz At-Taubah, Batam City. The goal is to analyze the principal's efforts in maintaining the effectiveness of school management, commitment, planning, organizing, implementing, supervising all educational programs, identifying obstacles, and explaining the results of implementing these commitments. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation, involving principals, teachers, and education staff. The results show that the principal's commitment is realized through strong vision and mission policy planning, consistency in decision making, exemplary behavior, and building a quality and achievement-oriented work culture. This commitment has positive implications for the success of school management, which is characterized by the realization of teacher performance, curriculum, resource optimization, and the creation of a conducive and religious school climate. Obstacles faced include limited funds, awareness of diverse school residents. However, strong commitment has been proven to have a positive impact. This study confirms that the principal's commitment is the main factor in maintaining the sustainability of the vision and mission of SMPIT in the Riau Islands Province.